Cancer-Associated Fibroblasts Influence the Biological Properties of Malignant Tumours via Paracrine Secretion and Exosome Production - Vokurka, Martin; Lacina, Lukáš; Brábek, Jan; Kolář, Michal; Ng, Yi Zhen; Smetana, Karel (International journal of molecular sciences, 2022)
Cancer-associated fibroblasts (CAFs) are an essential component of the tumour microenvironment. They represent a heterogeneous group of cells that are under the control of cancer cells and can reversely influence the cancer cell population. They affect the cancer cell differentiation status, and the migration and formation of metastases. This is achieved through the production of the extracellular matrix and numerous bioactive factors. IL-6 seems to play the central role in the communication of noncancerous and cancer cells in the tumour. This review outlines the role of exosomes in cancer cells and cancer-associated fibroblasts. Available data on the exosomal cargo, which can significantly intensify interactions in the tumour, are summarised. The role of exosomes as mediators of the dialogue between cancer cells and cancer-associated fibroblasts is discussed together with their therapeutic relevance. The functional unity of the paracrine- and exosome-mediated communication of cancer cells with the tumour microenvironment represented by CAFs is worthy of attention.
Keywords: exosome; Tumor Microenvironment; fibroblasty asociované s nádorem; Cell Movement; nádorové mikroprostředí; exozómy; interleukin-6; Interleukin-6; regulace genové exprese u nádorů; Cancer-Associated Fibroblasts; parakrinní signalizace; IL-6; cancer-associated fibroblast; Cell Proliferation; cancer microenvironment; Neoplasms; Paracrine Communication; Humans; Gene Expression Regulation, Neoplastic; pohyb buněk; nádory; Exosomes; proliferace buněk; cancer ecosystem; lidé